A New Kind of Spatial Inattention Associated With Chronic Limb Pain?. Issue 4 (4th March 2016) - Reid, Emily; Wallwork, Sarah B.; Harvie, Daniel; Chalmers, K. Jane; Gallace, Alberto; Spence, Charles; Moseley, G. Lorimer
Abstract : Pathological limb pain patients show decreased attention to some stimuli on the painful limb and increased attention to others, a paradox that has dogged the field for over a decade. We hypothesized that pathological pain involves a spatial inattention confined to bodily representations. Patients showed inattention to the painful side for visual processing of body parts but not letters, tactile processing but not auditory, and body‐part bisection tasks but not line bisection tasks. We propose the new term "somatospatial inattention" to describe bodily‐specific spatial inattention associated with pathological limb pain. Ann Neurol 2016;79:701–704